The reaction of Indonesian capital market to political event the announcement of Indonesia presidential election 2019 results: Event study on KOMPAS 100 - Ratnaningsih, Ni Made Dwita; Widanaputra, A. A. G. P. (International research journal of management, IT and social sciences, 2019)
Political events, especially the General Election is one of the non-economic risks that can influence investors' decisions to invest in the capital market. Elections are closely related to the policies that will be implemented by the elected President thus the elections are important for investors as the considerations for investment. This study aimed to determine the reaction of the Indonesian capital market by testing the information content of political events the announcement of the presidential election 2019 results using event study. The population in this study was all the companies that are listed in Indonesia Index KOMPAS 100, the sample was taken by the saturated sample method. The hypothesis was tested with one sample t-test. The announcement of the election results would contain the information that caused the market to react, as the evidenced there were significant abnormal returns occurred around the event window, and the average abnormal return that occur were positive, thus the announced election results that Jokowi-Ma'aruf’s victory was positively welcomed by the market